Effect of Yanshiqiangxin Decoction on Cardiomyocyte Apoptosis in Heart Failure Rats Based on PI3K/Akt/Caspase-9 Signaling Pathway - ZHU Sixing; YAN Shiyun; XU Yan; QIN Yan; CHEN Liyun; JIA Meijun (康复学报)
ObjectiveTo detect the effect of Yanshiqiangxin decoction on apoptosis of cardiomyocytes in rats with heart failure based on PI3K/Akt/Caspase-9 signalling pathway and to explore the possible mechanism of Yanshiqiangxin decoction in the treatment of heart failure.MethodsA total of 60 Wistar male rats were randomly divided into the normal group, the model group, the low dose Yanshiqiangxin decoction group, the medium dose Yanshiqiangxin decoction group,the high dose Yanshiqiangxin decoction group and the Perindopril group according to the random number table method, with 10 cases in each group. Except for the normal group, the remaining five groups were modelled by injecting adriamycin solution to induce myocardial injury and to establish the rat model of heart failure. In the low, medium and high dose Yanshiqiangxin decoction groups, 4.325, 8.65 and 17.3 g/(kg·d) of raw drug were administered by gavage respectively; the Perindopril group was given perindopril solution by gavage at the dose of 4 mg/(kg·d). The gavage dose was calculated as 10 mL/(kg·d) ,the normal group and the model group were given the same volume of distilled water. One day after the last gavage, M-mode echocardiography [left ventricular ejection fraction (LVEF), left ventricular short-axis shortening (LVFS), left ventricular internal dimension diastole (LVIDd) and left ventricular internal dimension systole (LVIDs)] was performed through an ultra-high resolution small animal ultrasound imaging system; B-type natriuretic peptide (BNP) was measured by ELISA method; the apoptosis of cardiomyocytes was observed through laser confocal microscopy and the apoptosis index was calculated; the expression of apoptosis-related proteins Bax, Bcl-2 and PI3K/Akt/Caspase-9 signalling pathway proteins were detected by Western blot method.Results① Cardiac ultrasound test results: compared with the normal group, the left ventricular anterior wall motion waveform of the model group was not obvious, close to linear motion, and LVEF and LVFS decreased significantly (P<0.05), LVIDd and LVIDs increased significantly (P<0.05), the left ventricle was significantly enlarged and the contractility was reduced. Compared with the model group, the amplitude of left ventricular anterior wall motion waveform increased at different degrees in the low, medium and high dose Yanshiqiangxin decoction group, LVEF and LVFS gradually increased with the increase of administration concentration (P<0.05), while LVIDd decreased only in the medium dose Yanshiqiangxin decoction group (P<0.05), LVIDs of the medium dose Yanshiqiangxin decoction group and the high dose Yanshiqiangxin decoction group were significantly reduced, the medium dose Yanshiqiangxin decoction group decreased the most significantly (P<0.05). ② Serum BNP results: compared with the normal group, BNP of the model group was significantly increased (P<0.05). Compared with the model group, BNP of the low, medium and high dose Yanshiqiangxin decoction group was significantly decreased, BNP gradually decreased with the increase of administration concentration (P<0.05). ③ Myocardial histopathology results: Cardiomyocytes had no apoptosis and almost no positive signal was detected in the normal group; compared with the model group,the number of cardiomyocyte apoptosis of the low, medium, high dose Yanshiqiangxin decoction group and the perindopril group was significantly decreased, the number of cardiomyocyte apoptosis gradually decreased with the increase of administration concentration (P<0.05). ④ PI3K/Akt/Caspase-9 signaling pathway protein expression levels and apoptotic factors: compared with the model group, PI3K and Akt protein expression, Bcl-2 content and Bcl-2/Bax ratio of the low, medium and high dose Yanshiqiangxin decoction group were significantly increased, PI3K and Akt protein expression, Bcl-2 content and Bcl-2/Bax ratio gradually increased with the increase of administration concentration (P<0.05); Caspase-9 and Caspase-3 protein expression of the low, medium and high dose Yanshiqiangxin decoction group were significantly decreased, Bax content of the medium and high dose Yanshiqiangxin decoction group were significantly decreased, and gradually increased with the increase of administration concentration (P<0.05).ConclusionsYanshiqiangxin decoction can improve cardiac function, reduce the content of BNP in serum and cardiomyocyte apoptosis, the mechanism may be related to the regulation of the PI3K/Akt/Caspase-9 signalling pathway.